Accuracy and Efficacy for Robotic Assistance in Implanting Responsive Neurostimulation Device Electrodes in Bilateral Mesial Temporal Lobe Epilepsy. Issue 3 (26th April 2017) - Chan, Alvin Y; Mnatsakanyan, Lilit; Sazgar, Mona; Sen-Gupta, Indranil; Lin, Jack J; Hsu, Frank P K; Vadera, Sumeet
Abstract: BACKGROUND: Responsive neurostimulation (RNS) is a relatively new treatment option that has been shown to be effective for patients with medically refractory focal epilepsy when resection is not possible, especially in bilateral mesial temporal onset. Robotic devices are becoming increasingly popular for use in stereotactic procedures such as stereoelectroencephalography, but have yet to be used when implanting RNS devices. OBJECTIVE: To show that these 2 forms of advanced technology were compatible and could be used effectively in patient care. METHODS: We implanted RNS devices in 3 patients with bilateral mesial temporal lobe epilepsy. Each patient was placed in the prone position, and electrode trajectories were planned via the robotic navigation system via a transoccipital approach. One lead was placed along each amygdalohippocampal complex. A small craniectomy was then created in the parietal region for RNS generator implantation. Actual and expected target locations and distance were calculated for each depth. There were no complications in this group. RESULTS: RNS devices with bilateral leads were successfully implanted in all 3 patients, with bilateral mesial temporal lobe onset. Follow-up ranged from 3 to 6 mo, and there were no complications in this group. The median distance between the estimate and actual targets was 2.18 (range = 1.11-3.27) mm. CONCLUSION: We show that implanting RNS devices with robotic assistance is feasible with excellent precision and accuracy. The advantages of using robotic assistance include higher flexibility, accuracy, precision, and consistency.